Global Ambition and Human Resource Reorientation of Indian and Malaysian Managers: Some Indicative Empirical Evidence - Chatterjee, Samir; Pearson, Cecil; Liu, Yi (SAGE Publications, 2013)
Transforming managerial competencies and mindsets is one of the most significant challenges facing contemporary Indian and Malaysian economies. This article provides empirical evidence demonstrating how managers in India and Malaysia are navigating the challenge of acquiring talented personnel to better facilitate central business activities in contemporary economic and cultural contexts. A salient theme of the article is that Indian and Malaysian managers are pursuing notions of human capital accumulation within a premise that the better deployment of resources is linked to an improvement in management systems and practices. The article posits that companies in the South East Asian landscapes are focusing on designing better selection and recruitment strategies to engage in continuous and innovative reform to cope with the demanding pressures of globalization.